Banks' Credit-Portfolio Choices and Risk-Based Capital Regulation - Caren Yinxia Nielsen (Lund University, School of Economics and Management, Department of Economics, 2016)
To address banks' risk taking during the recent financial crisis, we develop a model of credit-portfolio optimization and study the impact of risk-based capital regulation (Basel Accords) on banks' asset allocations. The model shows that, when a bank's capital is constrained by regulation, regulatory cost (risk weightings in the Basel Accords) alters the risk and value calculations for the bank's assets. The model predicts that the effect of a tightening of the capital requirements – for banks for which these requirements are (will become) binding – will be to skew the risky portfolio towards high-risk, high-earning assets (low-risk, low-earning assets), provided that the asset valuation – i.e., reward-to-regulatory-cost ratio – of the high-risk asset is higher than that of the low-risk asset. Empirical examination of U.S. banks supports the predictions applicable to the dataset. In addition, our tests show the characteristics of banks with different levels of risk taking. In particular, the core banks that use the internal ratings-based approach under Basel II invest more in high-risk assets.
Keywords: G11; G18; G21; G28; 330; Banks; asset risk; credit risk; portfolio choice; risk-based capital regulation